PERAN ORANG TUA TERHADAP PERKEMBANGAN BAHASA ANAK AUTIS USIA 4-5 TAHUN DI PAUD INKLUSI FAMILY CLUB 01 CIANJUR - Lilis Fitriyanti; Ilham Ramadhan; Ema Marhamah (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
Until now, the communication abilities of autistic children are still an obstacle in the interaction process, due to deficiencies in these abilities. Parents, as parties who have a major role in children's development, need to be actively involved in dealing with all developmental problems faced by their children. This research aims to understand the level of communication skills of autistic children and evaluate how the role of parents influences the development of autistic children aged 4-5 years at the Cianjur Family Club Inclusive PAUD. This research applies a qualitative approach by collecting data through observation, interviews and documentation studies conducted on parents of autistic children, autistic children and also school principals and Foundation Trustees at the Cianjur Family Club Inclusive PAUD. The results of the research revealed that the communication skills of autistic children aged 4-5 years at the Cianjur Family Club Inclusive PAUD focused on three main aspects, namely the first is speaking ability, where children experience difficulty in pronouncing words, however, children can already understand the delivery process. message. Second, the listening ability of autistic children is also quite good; Most children can grasp the expressions received, thanks to their fairly extensive vocabulary knowledge and their ability to demonstrate understanding of the messages received. And thirdly, the nonverbal speaking abilities of autistic children show better development than verbal communication. Children often use nonverbal movements as an effective form of communication. Subsequent research revealed that the role of parents is very important in the language development of autistic children aged 4-5 years at the Cianjur Family Club Inclusive PAUD. There are four main roles carried out by parents: caring, educating, nurturing, and providing love. They are aware of the limitations that autistic children have and feel it is very important to carry out these roles.